Deciphering Human Leukocyte Antigen Susceptibility Maps From Immunopeptidomics Characterization in Oncology and Infections - Juanes-Velasco, Pablo; Landeira-Viñuela, Alicia; Acebes-Fernandez, Vanessa; Hernández, Ángela-Patricia; Garcia-Vaquero, Marina L.; Arias-Hidalgo, Carlota; Bareke, Halin; Montalvillo, Enrique; Gongora, Rafael; Fuentes, Manuel (Frontiers in Cellular and Infection Microbiology, 2021)
Genetic variability across the three major histocompatibility complex (MHC) class I genes (human leukocyte antigen [HLA] A, B, and C) may affect susceptibility to infections. Individual genetic variation may help to explain different immune responses to microrganisms across a population. HLA typing can be fast and inexpensive; however, decipher peptides loaded in MHC-I and II, is requiring design and development of multiples methodological approaches and databases, which could help in the development of vaccines and identify high-risk HLA types to be prioritized for vaccination programs. Here, it is reviewed the recent developments and strategies in this field and discussed the next steps to promote translation into biomedicine.